A Look at the Liquidity Management Practices of Banks in South Africa - Tafirei Mashamba; Farai Kwenda (Journal of Economics and Behavioral Studies, 2017)
In an effort to strengthen bank liquidity-risk management practices, the Basel Committee proposed new liquidity requirements for banks in 2010 under the Basel III framework. However, despite the good intentions of the liquidity requirements the new regulations are likely to present some challenges for banks in the course of managing their liquidity. However, before any inference can be made about the possible implications of the liquidity standards on bank liquidity management practices, it is imperative to have insight into the current liquidity management strategies of banks. This paper seeks to determine the current liquidity management practices of banks in South Africa by examining whether South African banks have target liquidity levels which they pursue and also by determining the variables that drive bank liquidity ratios. The study sample comprised six commercial banks operating in South Africa over the period 1993 to 2009. For analysis, a partial adjustment model was developed and estimated using the generalized method of moments (GMM) estimator. The rate at which South African banks adjust their balance sheets was estimated at 8%. This adjustment speed implies that South African banks adjust their balance sheets slowly – probably due to high adjustment costs. Thus, South African listed banks have passively managed their liquidity and partially adjust their liquidity levels in an attempt to reach the optimal level. Furthermore, the following variables were considered to be the main drivers of liquidity ratios in South Africa: bank size, capital adequacy, loan loss reserves, and financial crisis.